2004
DOI: 10.1089/1096620041224148
|View full text |Cite
|
Sign up to set email alerts
|

The Cholesterol-Lowering Effect of Coconut Flakes in Humans with Moderately Raised Serum Cholesterol

Abstract: This study investigated the effect of coconut flakes on serum cholesterol levels of humans with moderately raised serum cholesterol in 21 subjects. The serum total cholesterol of subjects differed and ranged from 259 to 283 mg/dL. The study was conducted in a double-blind randomized crossover design on a 14-week period, consisting of four 2-week experimental periods, with each experimental period separated by a 2-week washout period. The test foods were as follows: corn flakes as the control food, oat bran fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…Trinidad et al [ 41 ] studied the effect of coconut flakes on the serum cholesterol levels of healthy individuals with moderately raised cholesterol levels of 259 to 283 mg. The test foods included coconut flakes which provided 15% and 25% dietary fiber from coconut.…”
Section: Discussionmentioning
confidence: 99%
“…Trinidad et al [ 41 ] studied the effect of coconut flakes on the serum cholesterol levels of healthy individuals with moderately raised cholesterol levels of 259 to 283 mg. The test foods included coconut flakes which provided 15% and 25% dietary fiber from coconut.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies should be carried out to help validate these significant benefits of consuming coconut milk and cream, and to determine whether such benefits are counteracted by any unfavourable changes to serum lipid profiles. In another study ( 172 ) , coconut flakes have been shown to reduce total cholesterol as well as LDL-C and serum TAG levels. Coconut residue after fluid extraction has a high percentage of soluble (3·41 g/100 g) and insoluble (34·0 g/100 g) dietary fibre ( 173 ) , and such high fibre content has been suggested to contribute to many of coconut's health benefits as in the coconut flake study mentioned above.…”
Section: Other Coconut Food Productsmentioning
confidence: 95%
“…These finding are consistent with the notion that the BBR effect plateaus and remains stable over a relatively long treatment time. In general, it appears that a minimum of 4 weeks of treatment is required in humans for the determination of stable lipid-lowering efficacy of a product [ 70 , 71 ]. In most studies, dietary restrictions were not applied or well controlled, e.g., the patients or participants maintained their normal dietary habits during the course of the studies.…”
Section: Lipid-lowering Efficacy Of Bbr In Humansmentioning
confidence: 99%